Umbilical temperature correlation with core and skin temperatures at rest, in the heat and during physical activity. (3rd October 2017) - Roberge, Raymond J.; Kim, Jung-Hyun; Yorio, Patrick; Coca, Aitor; Seo, Yongsuk; Quinn, Tyler; Aljaroudi, Ali; Powell, Jeffrey B.
Abstract: Purpose: to determine the correlation of umbilical temperatures (Tumb ) with simultaneously recorded chest wall temperature (Tchest ) and rectal temperature (Trectal ) in adults during rest, heat exposure and exercise. Methods: A total of 28 healthy men, wearing different types of clothing (athletic garb, a spandex full body heating garment, firefighter bunker gear) had average and peak umbilical, chest wall and rectal temperature measurements taken during sedentary temperature stabilisation stages, heat exposure periods and active exercise phases. Results: Curvilinear relationships were noted between Tchest and Tumb compared with Trectal and their association became noticeably positive and linear at approximately 35.5 °C. Polynomial regression analysis of Trectal with linear and quadratic forms of Tchest and Tumb indicated an overall R 2 of 0.657 and 0.767, respectively. Bivariate analysis of a restricted data set (where Tchest and Tumb ≥35.5°), indicated that Tumb was significantly associated with Trectal (raverage = 0.710, p <0.001; rpeak = 0.841, p <0.001) and Tchest was also significantly associated with Trectal, but less so (raverage = 0.570, p <0.001; rpeak = 0.699, p <0.001). Conclusions: the umbilicus offers a non-invasive, peripheral site for measurement of temperature that more closely correlated with body core temperature than Tchest when core temperature was ≥35.5 °C.